Low‐intensity pulsed ultrasound irradiation attenuates collagen degradation of articular cartilage in early osteoarthritis‐like model mice - Yoshitsugu Kojima; Takayuki Watanabe (Journal of Experimental Orthopaedics, 2023)
Abstract Purpose Osteoarthritis (OA) is a combination of degeneration and destruction of articular cartilage due to mechanical stress, secondary synovitis, and bone remodelling. In recent years, early knee OA, a preliminary stage of structural failure in OA, has attracted attention as a potential target for therapy to prevent the onset of OA. Intra‐articular administration of monoiodoacetic acid (MIA) induces OA‐like symptoms, and low doses of MIA induce early OA like symptoms. In this experiment, a low‐dose of MIA was induced to early OA model mice, which were then irradiated with low‐intensity pulsed ultrasound (LIPUS) to examine whether LIPUS improves symptoms of early OA. Methods After 4 weeks of LIPUS irradiation, articular cartilage was observed at 1 and 4 weeks. The Osteoarthritis Research Society International (OARSI) scores were calculated using Safranin‐O staining results. Cartilage degeneration was detected using Denatured Collagen Detection Reagent (DCDR). Results We observed a significant decrease in OARSI scores in the LIPUS irradiated group at week 4. The non‐LIPUS group showed widespread areas of double positivity for Type II collagen and DCDR, whereas the LIPUS group showed only a small number of DCDR‐positive areas. In addition, macrophage numbers counted in the articular capsule at week 1 showed a significant decrease in the LIPUS irradiated group. Lubricin detection showed that lubricin positive cell number was significantly increased by LIPUS irradiation at week 4. Conclusions These results suggest that LIPUS attenuates cartilage degeneration in early OA by relieving inflammation and enhancing the inhibitory effect of lubricin on cartilage degeneration.